Are we really so different, you and I? : male narration (Academic Video Online, 2012)
An Inspirational Diversity Meeting Opener Video. So often we focus on what makes us different, but in reality, there is far more that we have in common. This emotionally moving, inspirational video follows the circle of life as it highlights the common values and motivations that we share as human beings. A compelling way to start any diversity training program. Are We Really So Different, You and I? This will put your audience in the right frame of mind to discuss the critically important topic of diversity.